SERVICE QUALITY, PROMOTION OF CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE (Consumer case study of product Eiger Adventure Store Tamansiswa) - Henny Welsa; Putri Dwi Cahyani; Andi Ariyanto (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2023)
This study aims to determine the influence of independent variables, namely service quality and promotion, on the dependent variable customer loyalty with the intervening customer satisfaction variable. Influence testing in this study was carried out partially and simultaneously as well as a Sobel test to determine the influence of mediation variables. The study took samples from Eigerindo consumers who are in the Tamansiswa area. This research method uses a non-probability sampling technique with purposive sampling method. Data collection is carried out using a google form by distributing questionnaire links. The number of questionnaires processed is 100 and processed using SPSS 24. The data were analyzed using multiple linear regression analysis. The results showed that each independent variable affects the dependent variable, namely: 1) The service quality variable has a positive effect on customer satisfaction. 2) The promotion variable has no effect on customer satisfaction. 3) The variables of customer satisfaction and service quality have a positive effect on Eigerindo Tamansiswa's customer loyalty. 3) The promotion variable has no effect on Eigerindo Tamansiswa's customer loyalty.